"To Dispose of Wealth in Works of Charity": Entrepreneurship and Philanthropy in Medieval England. Issue 3 (2019) - Casson, Catherine; Casson, Mark
Abstract : While entrepreneurs are increasingly recognized as important participants in the medieval economy, their philanthropic activities have received less attention than those of the gentry and nobility. This article identifies the contribution that the study of medieval entrepreneurs can make to broader business history debates surrounding the identity of philanthropists and their beneficiaries, the types of causes they supported, and their impact on wider society. Philanthropic entrepreneurs used the profits of commerce to provide infrastructure, health care, and education to their local communities. Their patterns of philanthropy differed from those of gentry, lawyers, and administrators. Support for municipal infrastructure emerges as a distinctive feature of entrepreneurial philanthropy, reflecting a belief in the importance of trade networks and civic reputation.